2016
DOI: 10.11152/mu.2013.2066.183.kud
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femoral focal deficiency of the fetus – early 3D/4D prenatal ultrasound diagnosis

Abstract: Proximal Femoral Focal Deficiency (PFFD) is a rare congenital syndrome of unknown etiology. Additional disorders can be present up to 70% of PFFD cases. Management (including termination) depends on the severity of the malformation. We present a case of a 32-year-old woman referred for routine ultrasound examination in the 12 th week of pregnancy. Detailed 3D/4D evaluation revealed asymmetry of lower limbs and diagnosis of isolated PFFD was established. Parents were fully informed and decided to continue the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Proximal focal femoral deficiency is not commonly reported in medical literature due to the rarity of the condition. 2,13 Consequently, only few cases of PFFD have been reported in Nigeria, 4,5 and none of these was diagnosed prenatally; documentation of this patient case was, therefore, necessary. In addition, the prenatal ultrasound images of PFFD as presented may facilitate the recognition of the condition by other practitioners.…”
Section: Discussionmentioning
confidence: 97%
“…Proximal focal femoral deficiency is not commonly reported in medical literature due to the rarity of the condition. 2,13 Consequently, only few cases of PFFD have been reported in Nigeria, 4,5 and none of these was diagnosed prenatally; documentation of this patient case was, therefore, necessary. In addition, the prenatal ultrasound images of PFFD as presented may facilitate the recognition of the condition by other practitioners.…”
Section: Discussionmentioning
confidence: 97%
“…8,9,18,19 Our index patient did not have antenatal care, although antenatal ultrasound findings of similar cases were reported in many studies between 18 and 32 weeks' gestation. 1,2,7,11,[20][21][22] Kudla et al 23 reported a fetus as early as the 12th week of gestation whose ultrasound evaluation detected lower limb asymmetry and was diagnosed with…”
Section: Discussionmentioning
confidence: 99%
“…PFFD is a rare congenital anomaly consequent upon abnormal development of the femur in the trochanteric region with associated anomaly of the pelvis and lower limbs. Its incidence is 1-2/100 000 live births (Biko et al, 2012;Matsushita et al, 2014;Kudla et al, 2016). It is a radiological diagnosis without known genetic cause, but is established as an element of some skeletal dysplasias such as focal femoral hypoplasia.…”
Section: Discussionmentioning
confidence: 99%